2009
DOI: 10.1002/ijc.24253
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of the expression of RB18A/MED1, a cofactor of transcription, triggers strong tumorigenic phenotype of human melanoma cells

Abstract: The RB18A/MED1 human gene, also named TRAP220, DRIP205 and PBP, encodes for a single 205 kDa component, which interacts with nuclear receptors and transcription factors. RB18A/MED1 chromosome localization on locus 17q12-q21.1 suggests its involvement in human cancers. We herein analyzed RB18A/MED1 expression in human melanoma cell lines. We found that RB18A/ MED1 is either highly or weakly expressed in melanoma cells, depending on their respectively non or highly-tumorigenic phenotype. We therefore investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…Med1 has equivocal functions in different tumors. It functions as a tumor-suppressor gene and inhibits invasion and metastasis in lung carcinomas (27) and melanoma cells (28). Conversely, deficiency of Med1 protects hepatocytes from chemical carcinogen-induced hepatocarcinogenesis (29), and loss of Med1 significantly decreased proliferation of prostate cancer cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…Med1 has equivocal functions in different tumors. It functions as a tumor-suppressor gene and inhibits invasion and metastasis in lung carcinomas (27) and melanoma cells (28). Conversely, deficiency of Med1 protects hepatocytes from chemical carcinogen-induced hepatocarcinogenesis (29), and loss of Med1 significantly decreased proliferation of prostate cancer cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…Both protein complexes have already been shown to regulate melanoma development. The deletion of MED1, a component of the mediator complex, is known to increase melanoma aggressiveness (38). In the same way, when underexpressed in a cell line exhibiting a BRAF mutation (V600E) as in 501mel cells, SMARCB1, a component of the SMARC complex, prevents senescence and promotes melanomagenesis (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…The TRAP220 expression was elevated in half of the human prostate cancer tissues and TRAP220 plays a coregulatory role in the cell proliferation and survival of prostate cancer [24]. However, recent study revealed that TRAP220 knockdown in human melanoma cells in vitro increased the invasive properties and TRAP220 knockdown in melanoma cells in vivo switched the melanoma phenotype from non-tumorigenic to strongly tumorigenic in nude mice [25]. Furthermore, Gade et al showed that TRAP220-expressing A549 human lung adenocarcinoma cells formed significantly fewer metastases compared with the controls and a majority of primary lung cancer tissues showed a consistent loss of the TRAP220 and tumor metastasis suppressor DAPK1 expressions; this suggests that TRAP220 loss contributes to the attenuation of antitumor responses and the promotion of tumor growth [26].…”
Section: Covariatementioning
confidence: 96%